2015
DOI: 10.15448/1677-9509.2015.1.19830
|View full text |Cite
|
Sign up to set email alerts
|

A Feminização da Velhice: em foco as características socioeconômicas, pessoais e familiares das idosas e o risco social / The Feminization of Old Age: a focus on the socioeconomic, personal and family characteristics of the elderly and the social risk

Abstract: A Feminização da Velhice: em foco as características socioeconômicas, pessoais e familiares das idosas e o risco social 

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1
25

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 11 publications
4
8
1
25
Order By: Relevance
“…The case supports the results of previous investigations that qualified the WC measure as capable of better predicting the risk of cardiometabolic diseases 25 , including those in hidden situations 15 . A possible limitation of this study that should be considered is the exclusion of cutaneous fold measures, which could expand the discussion of the results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The case supports the results of previous investigations that qualified the WC measure as capable of better predicting the risk of cardiometabolic diseases 25 , including those in hidden situations 15 . A possible limitation of this study that should be considered is the exclusion of cutaneous fold measures, which could expand the discussion of the results.…”
Section: Discussionsupporting
confidence: 89%
“…The predominance of feminization in aging and in physical activity programs at the national level has been emphasized by previous studies 15,16 , highlighting the commitment of elderly women to health prevention.…”
Section: Resultsmentioning
confidence: 95%
“…Similar research to this study 13 attributes to the phenomenon of the feminization of aging, characterized by the greater search behavior of health presented by women and also by the high rate of male mortality during adulthood. Concomitant to this, according to data from the Brazilian Institute of Geography and Statistics 9 in Piauí, 51.2% of the population is composed of women, which reinforces the predominance of women in the research.…”
Section: Methodssupporting
confidence: 69%
“…This phenomenon was addressed in the above mentioned studies and has been labelled the feminization of the elderly. Several other studies 13,14 have addressed this issue, which deserves special attention given that we cannot interpret the fact that women live longer as meaning that they maintain a satisfactory quality of life and desirable health conditions. Until now at least, studies have shown that these variables are not associated in such a positive light.…”
Section: Discussionmentioning
confidence: 99%